2024
DOI: 10.1515/anly-2023-0068
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of Ψ-gamma, Ψ-beta and Ψ-hypergeometric matrix functions

Ashish Verma,
Komal Singh Yadav,
Bhagwat Sharan
et al.

Abstract: In this paper, we investigate the matrix analogues of the Ψ-beta and Ψ-gamma functions, as well as their properties. With the help of the Ψ-beta matrix function (BMF), we introduce the Ψ-Gauss hypergeometric matrix function (GHMF) and the Ψ-Kummer hypergeometric matrix function (KHMF) and derive certain properties for these matrix functions. Finally, the Ψ-Appell and the Ψ-Lauricella matrix functions are defined by applications of the Ψ-BMF, and their integral representations are also given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[29]). Traditional beta distributions were introduced in [11][12][13]28,30] using extended beta functions. They suggested that these distributions could help analyze and review techniques employed in specific circumstances during project evaluation and review.…”
Section: The Beta-logarithmic Distribution: Matrix Argumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…[29]). Traditional beta distributions were introduced in [11][12][13]28,30] using extended beta functions. They suggested that these distributions could help analyze and review techniques employed in specific circumstances during project evaluation and review.…”
Section: The Beta-logarithmic Distribution: Matrix Argumentsmentioning
confidence: 99%
“…Remark 6. The incomplete generalized beta-logarithmic matrix function in (55) can be reduced to numerous simple incomplete extended beta matrix functions (see, e.g., [4,13]).…”
Section: The Beta-logarithmic Distribution: Matrix Argumentsmentioning
confidence: 99%
See 1 more Smart Citation